Clap your hands - Cauley, Lorinda Bryan (New York : PaperStar Books, 1992)
Rhyming text instructs the listener to find something yellow, roar like a lion, give kiss, tell a secret, spin in a circle and perform other playful activities
Keywords: Play--Fiction; Stories in rhyme